Correlation Between Serum Zinc Levels and Severity of Acute Diarrhea in Children - Shahid Latif, Maria Risalat, Abdul Raheem, Farooq Ahmad Malik, Roomi Memon, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute diarrhea is one of the major causes of morbidity and mortality in children under the age of five years of age especially in developing countries. Zinc plays a vital role in immune functions, the mucosal integrity of the intestines and enzyme functions. The predisposition to infections and the duration of time in diarrhea has been associated with zinc deficiency. Place and Duration of Study: The study was carried out in the paediatric medicine department of The Children's Hospital Lahore from November 2022 to April 2023. Objective: To determine the correlation between the intensity of serum zinc and the degree of acute diarrhea in children. Methodology: A cross-sectional study was undertaken to examine paediatric patients (6 months to 5 years old) with acute diarrhea in a tertiary care hospital. The WHO sample size calculator formula was used to calculate the sample size. Consecutive sampling was used to enrol 120 patients. Informed consent was obtained and subsequently demographic and clinical data of each patient was recorded with the help of a structured proforma. The severity of the diarrhea in the patients was identified by the number of stools/days, degree of dehydration (as per the WHO guidelines) and period of the illness. Standardized laboratory procedures were used to measure serum zinc levels in the venous blood samples of each patient taken under aseptic conditions. Clinical examination based their division of the patients as mild, moderate and severe diarrhea. All the data collected were typed and calculated using appropriate statistical software. The connection between zinc in serum, and the severity of diarrhea in patients was determined by applying the relevant statistical tests with a p-value of less than 0.05 as the statistically significant value. Results: A total of 120 patients were included in the study. Mean serum zinc level was also significantly less in children with severe diarrhea, as opposed to mild and moderate ones (p < 0.05). The serum zinc levels showed negative relationship with the severity of diarrhea necessitating that reduced levels of zinc were correlated with the severity of the disease and the duration of diarrhea. Conclusion: Acute diarrhea is a highly severe disease whose severity is greatly linked to low serum levels of zinc in children. The use of zinc assessment and supplementation has the potential to be instrumental in the decreased disease burden and better clinical outcomes. Keywords: Serum zinc, acute diarrhea, children, dehydration, severity, pediatrics, deficiency, correlation